Surface-Active Thermally Responsive Hydrogels by Emulsion Sedimentation for Smart Window Applications - Timusk, Martin; Locs, Janis; Kangur, Triin; Kasikov, Aarne; Kurnitski, Jarek; Šutka, Andris (ACS applied polymer materials, 2023)
Thermally responsive polymers are a subject of increasing interest in research and development as a basis for a potential smart window technology. Here, we present a concept of preparing thermally responsive hydrogels with a thin active surface layer exhibiting rapid and reversible switching of light scattering in the visible and near-infrared spectral ranges. The process relies on the forced emulsion formation and sedimentation from the aqueous prepolymer solution by using a crosslinker that is engineered to serve as an antisolvent for the prepolymer and at the same time exhibit a suitable solubility profile in the sedimented hydrogel layer with respect to the supernatant aqueous phase. While the method can be employed for different polymer and crosslinker systems, as an example, here, we employ this concept for preparing thermally responsive hydrogels based on ethoxylated trimethylolpropane tri(3-mercaptopropionate) (ETTMP) and glycerol-derived crosslinkers with a dimaleate functionality, enabling crosslinking by the thiol-Michael click reaction. The material exhibits a luminous transmittance of over 95% and solar energy modulation of 59.91%. Moreover, we show that the pH and additives in the aqueous operating solution of the hydrogel enable the choice of the transition temperature in a wide range. The unique thin layer on the surface of the hydrogel, scalability to large surface areas, and robust and fast response at the practically relevant temperature range give this material a strong potential for smart window technology applications.